2011
DOI: 10.4236/ajac.2011.22016
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Analysis of the Responses to Partial Hepatectomy in Hepatocellular Carcinoma Patients

Abstract: In this study, liquid chromatography/quadrupole time of flight mass spectrometry (LC/QTOFMS) was employed for investigating the metabolome of the sera collected from hepatocellular carcinoma (HCC) patients before and 3 to 5 months after partial hepatectomy. To investigate the changes in metabolic phenotypes after the hepatic resection, principal components analysis (PCA) and support vector machine (SVM) were performed for the data grouping and classification. Based on the obtained SVM model, mass spectrometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…CYPs are estimated to be involved in the metabolism of drugs, chemicals and endogenous substrates, and hepatic CYPs may participate in the pathogenesis of liver diseases (51). Thus, the present results were in accordance with those from previous studies (47,51). …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…CYPs are estimated to be involved in the metabolism of drugs, chemicals and endogenous substrates, and hepatic CYPs may participate in the pathogenesis of liver diseases (51). Thus, the present results were in accordance with those from previous studies (47,51). …”
Section: Discussionsupporting
confidence: 94%
“…The present study revealed that HCC was correlated with several metabolic pathways, including purine metabolism and metabolism of xenobiotics by CYP. Purine metabolism may serve as the salvage pathway in HCC, as suggested by the upregulation of hypoxanthine, and the results reflected metabolic responses to surgical operation in HCC patients (47). In addition, the altered purine metabolism pathway provided a promising methodology to distinguish cirrhotic HCV patients who were at high risk of developing HCC from those who had already progressed to HCC (48).…”
Section: Discussionmentioning
confidence: 99%
“…Also, it is speculated that deteriorated liver function could cause reduced energy production through decreased amino acid synthesis and carnitine deficiency. This is because carnitine is synthesized endogenously from the essential amino acids 31 . Recent publication by Zhou et al discussed the differential metabolism of carnitines in serum and urine of patients with HCC and cirrhosis, and concluded that depending on the cause and the progression of liver damage, the acylcarnitines with short chain and long chain could show reverse accumulation in cirrhosis and HCC 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Mass spectrometry (MS) in combination with liquid chromatography (LC) is now widely used as an essential platform to perform global proteomic and metabolomic profiling of complex biological samples. For these applications, samples are commonly analyzed following a data-dependent acquisition (DDA, also referred to as information-dependent acquisition) approach. Despite being an efficient strategy to identify and quantify proteins or metabolites, the DDA technique still faces numerous challenges for the analysis of global protein expression or metabolite profiling due to its sampling bias toward high abundant precursor ions, which might hinder the selection of low abundant ones for fragmentation. , Therefore, a significant fraction of the precursor ions present in a complex mixture may not be identified.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] For these applications, samples are commonly analysed following a data-dependent acquisition (DDA, also referred to as information-dependent acquisition) approach. Despite being an efficient strategy to identify and quantify proteins or metabolites, the DDA technique still faces numerous challenges for the analysis of global protein expression or metabolite profiling due to its sampling bias towards high abundant precursor ions which might hinder the selection of low abundant ones for fragmentation.…”
mentioning
confidence: 99%